Cherry (Prunus avium) phenolic compounds for antioxidant preservation at food interfaces. (December 2018) - Basanta, Maria F.; Rojas, Ana M.; Martinefski, Manuela R.; Tripodi, Valeria P.; De'Nobili, Maria D.; Fissore, Eliana N.
Abstract: Cherry phenolics extracted by 90°C-water were loaded in a low-methoxyl-pectin (LMP) film for antioxidant preservation. Dark red films (pH = 3.46) contained flavonols (dihydrokaempferol-glucoside, quercetin-3- O -rutinoside), hydroxycinnamic acids (neochlorogenic, chlorogenic, 3- p -coumaroylquinic acids), and anthocyanins (cyanidin-3-O-glucoside, cyanidin-3-O-rutinoside), with a 6.97 × 10 −12  m 2 /s diffusion coefficient. Phenolics' stability was studied at constant relative humidity (RH: 57.7; 75.2%) and 25.0 °C. The pseudo-first-order de gradation rate was the highest ( t 1/2  = 3-2 months) and increased with the equilibration RH in darkness for anthocyanins, with simultaneous red vanishing by water nucleophilic attack. Instead, flavonols remained stable ( t 1/2 >1.5 years). Light (75.2%RH) induced the highest phenolics-degradation-rates, especially for anthocyanins ( t 1/2  = 11d), sensitizer, and film red color. Flavonols-decay was the slowest ( t 1/2  = 7–12 months). Antioxidant capacity paralleled phenolics-content. Hydroxycinnamic acids followed by flavonols could scavenge the singlet oxygen. Light-triggered LMP-matrix―phenolic interactions were determined, producing the lowest film water content and deformability. Cherry phenolics stabilized as a colored film constituted a food preserving antioxidant barrier. Highlights: Water-extractable cherry phenolics were loaded in a pectin film for preservation. Antioxidant capacity paralleled phenolics-stability at 57.7–75.2%RH in dark red film. Anthocyanins-loss was the fastest, together with film red color, and dependent on RH. Flavonols were stable in dark ( t 1/2 1.5 years), followed by hydroxycynnamic acids. Light (75.2%RH) raised phenolics-loss and led to film-matrix---phenolics interactions.